Are Relative Performance Measures in CEO Incentive Contracts Used for Risk Reduction and/or for Strategic Interaction? - Vrettos, Dimitris (The Accounting Review, 2013)
ABSTRACT: This study offers evidence that the use of RPE (Relative Performance Evaluation) in CEO incentive contracting depends on the type of strategic competition between a firm and its peers. Specifically, CEO pay is negatively (positively) associated with peer-group performance when firms compete as strategic substitutes (complements). This finding suggests that firms provide CEO incentives in order to influence strategic interaction with peer firms. Further, the directionally opposite pay-for-peer-group-performance sensitivities, i.e., negative (positive) for substitutes (complements), cancel each other in aggregate, which may explain the lack of consistent support found in prior research for the role of RPE in filtering out common noise from the CEO's performance. I also document that the weight on both substitute and complement peer performance increases, in absolute value, with the intensity of industry competition relative to the weight on own-firm performance. Finally, taking firms' explicit RPE disclosures into account does not affect the results.